After ever after - Sonnenblick Jordan 1969-; Jordan Sonnenblick (New York : Scholastic, 2010)
Although Jeff and Tad, encouraged by a new friend, Lindsey, make a deal to help one another overcome aftereffects of their cancer treatments in preparation for eighth-grade graduation, Jeff still craves advice from his older brother Stephen, who is studying drums in Africa.
O
820